Global flow fo funds analysis: Data, models, and applications - Zhang, Nan; Zhang, Nan (Singapore Springer Nature, 2024)
This book is the first to focus on the global flow of funds (GFF), providing an introduction to its fundamental concepts and establishing a theoretical framework for analysis. It connects the flow of funds within domestic economies to that of the rest of the world, offering a comprehensive analysis of GFF dynamics. This study enhances GFF statistics, enabling the assessment of global financial stability from both national and cross-border sectoral perspectives.